2021
DOI: 10.1186/s12882-021-02509-5
|View full text |Cite
|
Sign up to set email alerts
|

Case report: Osteomalacia due to bisphosphonate treatment in a patient on hemodialysis

Abstract: Background No publications have reported on osteomalacia in patients receiving intermittent cyclical therapy with etidronate (a bisphosphonate) and undergoing long-term hemodialysis (HD). Case presentation We report on a 46-year-old Japanese man admitted to our hospital for further examination of left forearm pain. Maintenance HD was started at age 24 years, and the man had been on HD since then. At age 38 years, surgical parathyroidectomy was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
0
0
Order By: Relevance
“…Another study from 2002 evaluated the use of etidronate on metastatic bone pain and discovered that an oral dose of 400mg/day for two weeks significantly reduced bone pain and suppressed bone resorption within 2 to 12 weeks after administration [29]. However, case studies have suggested potential complications such as osteomalacia due to longer exposure to etidronate in combination with other treatments [30,31].…”
Section: Etidronatementioning
confidence: 99%
“…Another study from 2002 evaluated the use of etidronate on metastatic bone pain and discovered that an oral dose of 400mg/day for two weeks significantly reduced bone pain and suppressed bone resorption within 2 to 12 weeks after administration [29]. However, case studies have suggested potential complications such as osteomalacia due to longer exposure to etidronate in combination with other treatments [30,31].…”
Section: Etidronatementioning
confidence: 99%